Influence of Marketing Mix on Purchasing Decisions at Rita Pasaraya Cilacap - Prihatin, Fitria; Jayanti, Esih (Prosiding University Research Colloquium, 2022)
The shift of society from shopping to traditional markets to modern markets (supermarkets) as a form of modernization. Amount supermarkets that have sprung up are also due to needs and desires sn increasingly large and diverse society. Supermarkets face very tough competition in terms of fighting over the number of existing customers/consumers. The supermarket manager has not fully understood consumer behavior overall to be able to maintain survival their supermarkets and can formulate their marketing strategies with quick and precise. In choosing a supermarket as a place to buy and meet needs, consumers are influenced by several factors-factors, including the marketing mix factor. Rita Pasaraya Cilacap is the first and complete supermarket in Cilacap. This study took the object of research on consumers Rita Pasaraya Cilacap with a sample of 102 respondents with random sampling technique and data collection through questionnaires. The data analysis technique used, namely validity test, reliability test, MSI (Method of Succesive Interval), assumption test classic (normality test, multicollinearity test and heteroscedasticity test), multiple linear regression analysis test, hypothesis testing (t test and F test) and analysis test coefficient of determination (R²). The results of the analysis show that the product, promotion and process partially have no significant effect on purchasing decisions. Meanwhile, price, place, employees and physical evidence partially have a significant effect on purchasing decisions. Simultaneously product, price, promotion, place, process, employee and physical evidence have a significant effect on purchasing decisions.